Invited review: Sensor technologies for real-time monitoring of the rumen environment - Han, Chan Su; Kaur, Upinder; Bai, Huiwen; Roqueto dos Reis, Barbara; White, Robin; Nawrocki, Robert A.; Voyles, Richard M.; Kang, Min Gyu; Priya, Shashank (Journal of dairy science, 2022)
Quantifying digestive and fermentative processes within the rumen environment has been the subject of decades of research; however, our existing research methodologies preclude time-sensitive and spatially explicit investigation of this system. To better understand the temporal and spatial dynamics of the rumen environment, real-time and in situ monitoring of various chemical and physical parameters in the rumen through implantable microsensor technologies is a practical solution. Moreover, such sensors could contribute to the next generation of precision livestock farming, provided sufficient wireless data networking and computing systems are incorporated. In this review, various microsensor technologies applicable to real-time metabolic monitoring for ruminants are introduced, including the detection of parameters for rumen metabolism, such as pH, temperature, histamine concentrations, and volatile fatty acid concentrations. The working mechanisms and requirements of the sensors are summarized with respect to the selected target parameters. Lastly, future challenges and perspectives of this research field are discussed.Quantifying digestive and fermentative processes within the rumen environment has been the subject of decades of research; however, our existing research methodologies preclude time-sensitive and spatially explicit investigation of this system. To better understand the temporal and spatial dynamics of the rumen environment, real-time and in situ monitoring of various chemical and physical parameters in the rumen through implantable microsensor technologies is a practical solution. Moreover, such sensors could contribute to the next generation of precision livestock farming, provided sufficient wireless data networking and computing systems are incorporated. In this review, various microsensor technologies applicable to real-time metabolic monitoring for ruminants are introduced, including the detection of parameters for rumen metabolism, such as pH, temperature, histamine concentrations, and volatile fatty acid concentrations. The working mechanisms and requirements of the sensors are summarized with respect to the selected target parameters. Lastly, future challenges and perspectives of this research field are discussed.